Between angels and demons: boundary symbols and symbolic politics in the Danish management of aliens - Hedetoft, Uld Riber (Politik, 2010)
This article will engage with some of the political symbols and the symbolic politics which over the last decade have been developed in aid of the con rmation and reassertion of the borders between ‘them’ and ‘us’ in Denmark – and the ways such border and boundary symbols get deployed as discursive weapons in the ght against a threat which sometimes is demonized as both internal and external, but more and more frequently get played down, modi ed or even neutralized in the context of more pragmatic perceptions of integration. In consequence of this current tendency, the paper will nally discuss not only the symbolic politics of boundaries, but also new developments constraining the usefulness of old-style symbolic politics while in the process introducing new boundaries and di erent political priorities.